Institutional Resilience in Hajj and Umrah in Southeast Asia: Integration of Good Corporate Governance (GCG) as a Pillar of Stability in Economic Crisis - Adri; Febriani, Eli; Baginda Parsaulian (ICIEFS Proceeding, 2025)
This study aims to analyze the institutional resilience of the implementation of Hajj and Umrah in Southeast Asia through the application of the principles of Good Corporate Governance (GCG) as a pillar of stability during economic crises. Hajj management institutions in Indonesia, Malaysia, and Brunei Darussalam face challenges due to global economic fluctuations, regulatory changes, and socio-political dynamics of Muslims. In this situation, the implementation of GCG is an important element to ensure transparency, accountability, responsibility, independence, and fairness in institutional governance. Using a qualitative approach and comparative studies, this study shows that GCG integration can improve the efficiency of hajj fund management, strengthen public trust, and maintain operational sustainability amid economic pressure. Harmonization between national regulations, sharia principles, and ethical investment policies is the key to institutional stability and long-term resilience of the implementation of Hajj and Umrah in the region.